Novel resveratrol nanodelivery systems based on lipid nanoparticles to enhance its oral bioavailability - Neves, Ana Rute (Dove Medical Press, 2013)
INTRODUCTION: Resveratrol is a polyphenol found in grapes and red wines. Interest in this polyphenol has increased due to its pharmacological cardio- and neuroprotective, chemopreventive, and antiaging effects, among others. Nevertheless, its pharmacokinetic properties are less favorable, since the compound has poor bioavailability, low water solubility, and is chemically unstable. To overcome these problems, we developed two novel resveratrol nanodelivery systems based on lipid nanoparticles to enhance resveratrol’s oral bioavailability for further use in medicines, supplements, and nutraceuticals. METHODS AND MATERIALS: Solid lipid nanoparticles (SLNs) and nanostructured lipid carriers (NLCs) loaded with resveratrol were successfully produced by a modified hot homogenization technique. These were completely characterized to evaluate the quality of the developed resveratrol-loaded nanoparticles. RESULTS: Cryo-scanning electron microscopy morphology studies showed spherical and uniform nanoparticles with a smooth surface. An average resveratrol entrapment efficiency of ~70% was obtained for both SLNs and NLCs. Dynamic light scattering measurements gave a Z-average of 150–250 nm, polydispersity index of ~0.2, and a highly negative zeta potential of around −30 mV with no statistically significant differences in the presence of resveratrol. These characteristics remained unchanged for at least 2 months, suggesting good stability. Differential scanning calorimetry studies confirmed the solid state of the SLNs and NLCs at both room and body temperatures. The NLCs had a less ordered crystalline structure conferred by the inclusion of the liquid lipid, since they had lower values for phase transition temperature, melting enthalpy, and the recrystallization index. The presence of resveratrol induced a disorder in the crystal structure of the nanoparticles, suggesting a favoring of its entrapment. The in vitro release studies on conditions of storage showed a negligible resveratrol release over several hours for both nanosystems and the in vitro simulation of gastrointestinal transit showed that the resveratrol remained mostly associated with the lipid nanoparticles after their incubation in digestive fluids. CONCLUSION: Both nanodelivery systems can be considered suitable carriers for oral administration, conferring protection to the incorporated resveratrol and allowing a controlled release after uptake.